Acute effects of insulin and insulin-induced hypoglycaemia on carotid body chemoreceptor activity and cardiorespiratory responses in dogs - Baby, Santhosh M. (2022)
Funding: Silvia V. Conde declares that Galvani Bioelectronics provided funds to support their work associated with Type 2 diabetic project.